The Dual of a Hyperbolic Approximation to the Generalized Constrained Multi-Facility Location Problem with lp, Distances - Love, Robert F. (Management Science, 1974)
This article develops the dual program corresponding to a hyperbolic approximation, of the constrained multi-facility location model using l p distances. The dual program is original and is a contribution to the theory of facilities location as well as providing a new efficient method of computing optimal facilities location in certain cases where linear constraints are present. Some properties of the dual are developed as the hyperbolic approximation model converges to the actual location model. Computation results using a decomposition programming method are given and discussed.